Sex Determination Using Morphometric and Morphological Dimensions of the Clavicle within the KwaZulu-Natal Population - Ishwarkumar,S (Sociedad Chilena de Anatomía, 2016)
Sex determination plays an essential role in forensic anthropology in the identification of an individual from skeletal remains. The aim of the study was to determine sex of an individual using the clavicle in a KwaZulu-Natal population. Various morphometric and morphological parameters were measured using 100 clavicles of known sex (66 male and 34 female) and age (range 2595 years). The mean maximum length, mid-shaft circumference and maximum breadth of the sternal and acromial ends of the male clavicles were greater in females. However, the mean medial curve of the clavicle was greater in females than in males on both sides, and on the right side the female clavicles also had a greater mean lateral curve than the males. The maximum length and mid-shaft circumference alone could be used to predict sex with an accuracy of 89 %. Therefore, the provision of morphometric data pertaining to the clavicle may assist forensic investigators, anthropologists and anatomists to sex the clavicle.